Outbreak of multidrug-resistant tuberculosis in South Africa undetected by WHO-endorsed commercial tests: an observational study. Issue 12 (December 2018) - Makhado, Ndivhuho A; Matabane, Edith; Faccin, Mauro; Pinçon, Claire; Jouet, Agathe; Boutachkourt, Fairouz; Goeminne, Léonie; Gaudin, Cyril; Maphalala, Gugu; Beckert, Patrick; Niemann, Stefan; Delvenne, Jean-Charles; et al.
Summary: Background: Global roll-out of rapid molecular assays is revolutionising the diagnosis of rifampicin resistance, predictive of multidrug-resistance, in tuberculosis. However, 30% of the multidrug-resistant (MDR) strains in an eSwatini study harboured the Ile491Phe mutation in the rpoB gene, which is associated with poor rifampicin-based treatment outcomes but is missed by commercial molecular assays or scored as susceptible by phenotypic drug-susceptibility testing deployed in South Africa. We evaluated the presence of Ile491Phe among South African tuberculosis isolates reported as isoniazid-monoresistant according to current national testing algorithms. Methods: We screened records of 37 644 Mycobacterium tuberculosis positive cultures from four South African provinces, diagnosed at the National Health Laboratory Service–Dr George Mukhari Tertiary Laboratory, to identify isolates with rifampicin sensitivity and isoniazid resistance according to Xpert MTB/RIF, GenoType MTBDR plus, and BACTEC MGIT 960. Of 1823 isolates that met these criteria, 277 were randomly selected and screened for Ile491Phe with multiplex allele-specific PCR and Sanger sequencing of rpoB . Ile491Phe-positive strains (as well as 17 Ile491Phe-bearing isolates from the eSwatini study) were then tested by Deeplex-MycTB deep sequencing and whole-genome sequencing to evaluate their patterns of extensive resistance, transmission, and evolution. Findings: Ile491Phe was identified in 37 (15%) of 249 samples with valid multiplex allele-specific PCR and sequencing results, thus reclassifying them as MDR. All 37 isolates were additionally identified as genotypically resistant to all first-line drugs by Deeplex-MycTB. Six of the South African isolates harboured four distinct mutations potentially associated with decreased bedaquiline sensitivity. Consistent with Deeplex-MycTB genotypic profiles, whole-genome sequencing revealed concurrent silent spread in South Africa of a MDR tuberculosis strain lineage extending from the eSwatini outbreak and at least another independently emerged Ile491Phe-bearing lineage. Whole-genome sequencing further suggested acquisition of mechanisms compensating for the Ile491Phe fitness cost, and of additional bedaquiline resistance following the introduction of this drug in South Africa. Interpretation: A substantial number of MDR tuberculosis cases harbouring the Ile491Phe mutation in the rpoB gene in South Africa are missed by current diagnostic strategies, resulting in ineffective first-line treatment, continued amplification of drug resistance, and concurrent silent spread in the community. Funding: VLIR-UOS, National Research Foundation (South Africa), and INNOVIRIS.